Tropopause fold observation by MARA VHF wind-profiler radar and their occurrence rates over the Antarctic station Troll (72°S, 2.5°E) - Maria, Mihalikova; Sheila, Kirkwood (2013)
第4回極域科学シンポジウム 横断セッション：[IM] 中層大気・熱圏 11月13日（水） 国立極地研究所 2階大会議室 conference object